On the antihistaminic effects of sympathine E (Revista Española de Fisiología, 1948)
Several kinds of experiments have been made to confirm the anthistaminic activity of sympatin E. The sympatin extracts show in all experiments, like adrenaline, a strong antihistaminic power. It persists for several days after injection (at least for 12 days in the rabbits tested).